2006
DOI: 10.1037/0021-843x.115.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Frontal EEG asymmetry and premenstrual dysphoric symptomatology.

Abstract: Resting frontal electroencephalographic (EEG) asymmetry has been hypothesized to tap a diathesis toward depression or other emotion-related psychopathology. Frontal EEG asymmetry was assessed in college women who reported high (n = 12) or low (n = 11) levels of premenstrual negative affect. Participants were assessed during both the follicular and the late luteal phases of the menstrual cycle. Women reporting low premenstrual dysphoric symptomatology exhibited greater relative left frontal activity at rest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 29 publications
3
30
0
1
Order By: Relevance
“…Asymmetry scores did not differ for control or PMDD participants outside of the luteal phase, but scores for the PMDD group fell into the negative range (less left frontally active) during the luteal period while the control participants remained stable. In contrast, Accortt and Allen (2006) used a larger unmedicated sample, with carefully timed late luteal and follicular visits by women either high or low in self-reported premenstrual negative affect. Women reporting high pre-menstrual distress (n=12) exhibited significantly less relative left frontal-temporal activity at rest than women low in pre-menstrual distress (n=11), regardless of the phase of cycle (follicular versus luteal).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymmetry scores did not differ for control or PMDD participants outside of the luteal phase, but scores for the PMDD group fell into the negative range (less left frontally active) during the luteal period while the control participants remained stable. In contrast, Accortt and Allen (2006) used a larger unmedicated sample, with carefully timed late luteal and follicular visits by women either high or low in self-reported premenstrual negative affect. Women reporting high pre-menstrual distress (n=12) exhibited significantly less relative left frontal-temporal activity at rest than women low in pre-menstrual distress (n=11), regardless of the phase of cycle (follicular versus luteal).…”
Section: Introductionmentioning
confidence: 99%
“…Women reporting high pre-menstrual distress (n=12) exhibited significantly less relative left frontal-temporal activity at rest than women low in pre-menstrual distress (n=11), regardless of the phase of cycle (follicular versus luteal). These pilot studies suggested the possibility of a common diathesis for both major depression and premenstrual dysphoria (Accortt & Allen, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, prefrontal brain asymmetry appears to be an important risk factor not only for MDD, but also for internalizing disorders more generally, all of which are associated with a predisposition toward high levels of negative affect. In addition to depression, frontal EEG asymmetry has been found to characterize those with: anxious arousal/somatic anxiety (Mathersul, et al, 2008; Nitschke, Heller, Palmieri, & Miller, 1999; Stewart, Levin-Silton, Sass, Heller, & Miller, 2008); panic disorder (Wiedemann, Pauli, Dengler, Lutzenberger, Birbaumer, & Buchkremer, 1999); comorbid anxiety and depression (Bruder, Fong, Tenke, Leite, Towey, & Stewart, 1997); social phobia (Davidson, Marshall, Tomarken, & Henriques, 2000); premenstrual related dysphoria (Accortt & Allen, 2006; Accortt, Stewart, Towers, & Allen, 2009), seasonal affective disorder (Allen, et al, 1993), ), and a variety of childhood or adolescent internalizing psychopathology (Buss, et al, 2003, Fox, et al, 1995 Henderson, Marshall, Fox, & Rubin 2001, Schmidt & Fox, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Both MDD (Kendler et al, 2006) and PMDD (Treloar et al, 2002) have heritable risk, suggesting the possibility that both PMDD and MDD share common risk mechanisms (Accortt et al, 2006; Accortt et al 2011b). …”
Section: Introductionmentioning
confidence: 99%